Večsmernost začetkov slovenske operne ustvarjalnosti - Barbo, Matjaž (Muzikološki zbornik, 2007)
The paper deals with operatic production in Slovenia in the watershed period at the turn of the 19th century. It focuses on the work of F. B. Dusík; in particular, three of his key works, which, according to newly available facts, were written during his sojourn in Ljubljana: Sultan Wampum, Eugen der zweyte oder Der Held unserer Zeit and Die Lederers Tochter oder Der weibliche Kadet, all of which were also performed in Ljubljana. Although they are labelled operas, their form bears more similarity to the Singspiel with spokendialogues. Thus on first view they could be ascribed to the ever more explicit nationalist movement, according to which we can trace an increase in regular appearances of the companies of German impresarios, which by the last decade of the 18th century completely overshadow the previously ubiquitous Italian operatic companies. Nonetheless, their resemblance to the farce - the form to which Dusík later devotes himself - most likely points to the more general aesthetic turn of the time. These works demonstrate the astonishing continuity of operatic output and the regular cooperation of local musicians in opera, providing an image of the rich operatic production of this period in Slovenia.
Keywords: Dusík, Franz Benedikt, 1766-1816; glasba; music; narodna zavest; singspiel; slovenska opera